ANALYSIS OF THE IMPACT OF IMPLEMENTING SCHOOL ZONING POLICIES ON INCREASING ACCESS TO EDUCATION - Loso Judijanto; Rhisty Frida Utami; Dina Destari (International Journal of Teaching and Learning, 2025)
This research analyzes the impact of implementing school zoning policies on increasing access to education. The zoning policy, adopted by the Ministry of Education and Culture, aims to reduce educational inequality and encourage equal distribution of education quality across regions. The research results show that zoning policies have succeeded in increasing equitable access to education by ensuring students can go to school near where they live. This reduces the economic burden on families and increases learning opportunities for students from various socio-economic backgrounds. Apart from that, this policy also encourages equal distribution of educational resources, including the availability of teachers and educational facilities. However, research also finds that there are a number of challenges that need to be overcome to ensure the effectiveness of zoning policies. The main challenges include disparities in the quality of teaching staff in various zones, administrative and regulatory complexities, and uneven adaptation to educational technology. The need for uniform regulation, redistribution of teachers, and improvement of technological infrastructure are the main recommendations of this research. Overall, school zoning policies have great potential to improve access and quality of education, but require continued support and collaborative efforts from various parties to overcome existing challenges and ensure effective implementation.